2023
DOI: 10.3390/jcm12123944
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Irrigation System to Reduce Heat Generation during Guided Implantology: An In Vitro Study

Abstract: The purpose of this in vitro study is to evaluate the effectiveness of incorporating a new irrigation system into a surgical guide and monitor its effect on heat generation during implant bed preparation. A total of 48 surgically guided osteotomies were performed on 12 bovine ribs divided into 4 groups, using different irrigation techniques: Group A (test) had entry and exit channels incorporated into the guide; Group B had a similar design with an entry channel only; Group C had conventional external irrigati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Our results align with a recent study by Parvizi et al [29], who designed a multichannel surgical guide for drilling adjacent implants. This guide featured a built-in irrigation channel and an exit irrigation channel.…”
Section: Discussionsupporting
confidence: 92%
“…Our results align with a recent study by Parvizi et al [29], who designed a multichannel surgical guide for drilling adjacent implants. This guide featured a built-in irrigation channel and an exit irrigation channel.…”
Section: Discussionsupporting
confidence: 92%
“…While numerous technical studies have explored methods to mitigate the heat effects on bone, such as utilising coolant irrigation, optimising drill bit geometry [9], enhancing wear resistance [47], implementing step-power drilling [48], etc., there is no conclusive evidence to indicate that irrigation cooling is universally adopted as a standard practice, despite strong recommendations from major implant manufacturers. However, clinically, irrigation cooling is standard practice and is strongly advocated for by leading implant manufacturers [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, less attention has been paid to measurements of the intraosseous temperature increments caused by osteotomy guided by templates with built-in irrigation pipes. To our knowledge, this problem has been addressed by three studies so far [24][25][26]. Stocchero et al tested surgical guides with internal cooling on bovine rib specimens and did not find any benefits compared to classical guides [25].…”
Section: Introductionmentioning
confidence: 98%
“…Teich et al, on the other hand, demonstrated significantly more effective cooling when the irrigation fluid was guided toward the osteotomy site via a pair of internal irrigation fluid channels [26]. Parvizi et al conceived an internally cooled surgical guide that incorporated both an entry and exit channel for the cooling agent and found a significant reduction in the intraosseous temperature [24] within the experimental framework employed previously by Stocchero et al [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation